Prognostic Significance of Peripheral Artery Disease in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Yihua Xia; Kangning Han; Yujing Cheng; Zhijian Wang; Fei Gao; Xiaoteng Ma; Yujie Zhou (Reviews in Cardiovascular Medicine, 2023)
Background: Peripheral artery disease (PAD) elevates the risk of adverse outcomes. The current work aimed to evaluate the influence of PAD in acute coronary syndrome (ACS) cases administered percutaneous coronary intervention (PCI), and to determine whether PAD adds incremental prognostic value to the global registry of acute coronary events (GRACE) scale. Methods: To retrospectively analyze a single-center, prospective cohort trial, we consecutively included ACS cases administered PCI. Individuals with and without PAD were comparatively examined for clinical outcomes. The primary endpoint was major adverse cardiovascular events (MACEs), a compound item encompassing all-cause death, myocardial infarction (MI), stroke and repeat revascularization. The added value of PAD based on a reference model was examined. Results: PAD was detected in 179 (10.4%) of the 1,770 included patients. The incidence rates of MACEs (40.3% vs. 17.9%), all-cause death (11.2% vs. 1.6%), cardiovascular death (8.9% vs. 1.4%), MI (8.4% vs. 2.2%) and repeat revascularization (30.2% vs. 15.2%) were all markedly elevated in PAD cases in comparison with the non-PAD group (p < 0.001). After adjusting for other confounding variates, PAD independently predicted MACE occurrence (hazard ratio = 1.735, 95% confidence interval: 1.281–2.351). Addition of PAD resulted in remarkably increased predictive performance for MACE compared to the baseline GRACE score (Harrell’s C-statistic: 0.610 vs. 0.587, p < 0.001; net reclassification improvement: 0.134, p < 0.001; integrated discrimination improvement: 0.035, p < 0.001). Conclusions: In ACS cases administered PCI, PAD independently worsens clinical outcomes and adds incremental value to the GRACE risk score.